Forging a Linguistic Identity, Overseas-trained South Asian Doctors in the UK - Farooq, Dr Yasmin Ghazala (Border Crossing, 2021)
Contemporary social policy debates on community cohesion in the UK appear to have very prescribed identities for migrants centred around on concepts of ‘Britishness’, having ‘common values’ and one national language, that is, English, for their successful integration. This paper draws on an empirical study of the integration and identity experiences of overseas-trained South Asian Doctors in the UK. The study involved in-depth interviews with 27 overseas-trained South Asian doctors practicing as general practitioners (GPs) in three geographical locales with varying ethnic density and urban/rural mix in the UK. The study set out to explore how this group of highly skilled migrants integrated into the UK society, perceived their identities and whether they had acquired a sense of belonging to Britain. The key concepts examined included identity, context of migration, structural and socio-cultural integration. Their narratives show that while they drew on certain sections of British society for recognition and realisation of opportunity by embedding themselves in local social contexts, they also drew strength from their own religious/cultural and linguistic resources. This included engaging with the revolutionary writings of their own poets and scholars as a way of creative thinking, innovating and dealing with adversity. In addition to the adaptation and dealing with adversity in the UK, the evidence shows that South Asian languages have played a significant role in maintaining transnational identities.